(untitled) (Training and Practice : Journal of Educational Sciences, 2021)
The aim of the study was to examine the overal well-being of kindergarten teachers, and its relation to the employment characteristics, parameters of workplace, satisfaction with work environment, effort-reward imbalance, work-family conflict, and self-rated health. Our results revealed that kindergarten teachers with lower rates of overall well-being 1) reported impaired physical health, 2) work with groups including more children, 3) are less satisfied with their work environment, 4) showed more work related stress characterized by the imbalance of efforts, rewards, and overcommitment, and 4) have more work-family conflict.